The Impact of Sustainable HRM on Organization’s Reputation - Mobarez, Ayman (The Arab Journal of Administration, 2020)
This conceptual research examines how Sustainable Human Resource Management (Sustainable HRM) can help establishing an attractive employer brand that can address the different needs and expectations of potential and existing employees, without compromising a consistent employer image, which can result in a sustained competitive advantage. Sustainable HRM should help firms attract and retain high-quality employees, because by integrating Sustainable HRM practices into the employee value Proposition, they establish a unique, attractive employer brand. An extended employee life cycle concept depicts how the employer brand promise can be delivered to address the different needs and expectations of potential and existing employees. The research question: How Sustainable Human Resource Management (Sustainable HRM) can help establishing a positive perceptions of an organization’s reputation that can address the different needs and expectations of potential and existing employees, without compromising a consistent employer image, which can result in a sustained competitive advantage. Research goals: The research has been undertaken to achieve the following objectives: 1- Contribute to the ongoing debate about the link between sustainability and HRM by analyzing how Sustainable HRM functions help attracting and retaining high-quality employees, which in turn can enable a sustained competitive advantage. 2- Provides a framework for how Sustainable HRM supports the positive perceptions of an organization’s reputation to enhance employer attractiveness. 3- To shows how integrating Sustainable HRM into the a positive perceptions of an organization’s reputation enables addressing the diverse needs and expectations of potential and existing employees in varying life and career stages.